THE INFLUENCE OF GREEN PRODUCTS ON GREEN MARKETING AND SUSTAINABLE TOURISM - Yudawisastra, Helin; Hapsari, Ayuningtyas; Purliantoro, Dwi; Qamri, Ghulam; Hanim, Wasifah (TRIKONOMIKA, 2025)
Sustainable tourism is becoming an important priority in the development of tourist destinations, which are facing environmental challenges. This research aimed to explore the influence of green products on sustainable tourism in the Bandung tourist area, where green marketing serves as a moderating factor. Quantitative methods combined with descriptive verification were used to survey several tourist attractions that have implemented the concept of green tourism. The respondents comprised 210 visitors and the multivariate data analysis method was factor analysis with covariance-based SEM-PLS using SmartPLS. The results show that green products independently influence sustainable tourism from green marketing as a moderating variable. Green products influence the ability of tourist attractions in the Bandung area to continue operating because the local community has the knowledge and cares for this industry. As a result, this understanding will increase trust in tourism sector for both tourist and companies offering the services.